Visualization and monitoring information management of bridge structure health and safety early warning based on BIM. Issue 2 (4th March 2022) - Deng, Langni; Lai, Shijin; Ma, Jinchao; Lei, Lizhen; Zhong, Mengjun; Liao, Ling; Zhou, Zheng
ABSTRACT: Bridge structure health assessment has become a research hotspot. However, the traditional methods lack unified integrated management of the health monitoring related information during the whole life of the bridge, and the visualization of the monitoring information is low. This study proposes a BIM-based bridge health state safety warning and information integration management method which takes Revit software as the development platform and integrates the functional plug-ins of visual warning and monitoring information management into the Revit software through Revit API interface. The implementation of this method is to create a virtual sensor system, forming a monitoring information model, thus forming a front-end visualization carrier. The back-end monitoring information integrated management platform is constructed based on database technology, and the BIM model is associated with monitoring data, so that the management of monitoring information storage, viewing and analysis can be carried out from Revit platform, which further improves the integration and visualization management level of monitoring information. Taking the health monitoring project of Ge Xian Bridge, Yizhou City, Guangxi Province, China as an example, the study describes the implementation of each functional module. Graphical Abstract: uf0001